Case Study : Air Terjun Laundry / Nurul Athirah Anuar - Anuar, Nurul Athirah (2020)
Air Terjun Laundry is a business that provide facility of self-service to wash and dry the clothes without much personalized professional help. It is a well-known self-service laundry at Lembah Sireh since it is the biggest laundry shop at Kota Bharu and has been operating for 6 years. The facilities offered by Air Terjun Laundry including user-friendly coin-operated washing machines, dryers and Wi-Fi. There is also a vending machine for the customers to buy drinks